A Drug Screening Platform for Podocytopathies in Drosophila Nephrocytes. - Spitz, D.; Wiggering, J.; Prakash, C.; Ulbrich, M.H.; Schneider, R.; Hermle, T. (Journal of the American Society of Nephrology, 2025)
Background: The complex cellular architecture of the glomerular filtration barrier is not recapitulated in vitro, representing a major obstacle for drug screening. This contributes significantly to a therapeutic gap for the heterogeneous diseases affecting the podocyte. Phenotypic drug screening using whole organisms is inherently slow but can reveal entirely unexpected therapies that are unattainable by conventional screening. The Drosophila nephrocyte features a molecularly conserved filtration barrier, suitable for whole-animal screening in podocytopathies. Methods:We generated transgenic Drosophila expressing a secretable variant of green fluorescent protein as a genetically encoded tracer for rapid analysis of nephrocyte function. Animals were exposed to drugs in liquid food before recording nephrocyte fluorescence intensity. The slit diaphragm architecture was investigated using immunofluorescence and subsequent automated quantification. Results: The genetically encoded tracer, combined with fast detection through enhanced widefield fluorescence microscopy, provided a faster but reliable screening assay for nephrocyte function compared with the established approach using FITC-albumin ex vivo. Rac1 is a key regulator of the actin cytoskeleton, involved in maintaining podocyte structure and function. In nephrocytes, overexpression of Rac1 resulted in mislocalization of slit diaphragm proteins and deeper membrane invaginations. Since nephrocyte function was further decreased as detected by the novel assay, we used this screening background relevant to podocyte biology for a pilot screen of 100 drugs. We identified significant improvement of nephrocyte function for zacopride, a respective agonist or antagonist of serotonin receptors, which restored the slit diaphragm architecture despite overexpression of Rac1. The mechanism of action of zacopride appeared independent from the orthologs of the mammalian target proteins or direct Rac1 inhibition, suggesting a pleiotropic target. This hit from the pilot screen illustrates the potential of phenotypic drug screening to reveal unexpected therapeutic options. Conclusions: We present a proof of concept for whole-animal drug screening using podocyte-like Drosophila nephrocytes.